Hubungan Lokasi Insersi Pemasangan Infus Dan Kejadian Flebitis (Systematic Literature Review) - Solehudin Solehudin; Astrid Novita; Risha Gustiani Hamzah (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Introduction : Central Line Associated Blood Stream Infection (CLABSI) or phlebitis is defined by the CDC as a bloodstream infection confirmed by laboratory results that occurs within 48 hours before developing into bacteremia, and is not associated with infection in other parts. Some research results conclude that several factors influence the occurrence of phlebitis, one of which is the selection of the insertion site. Purpose: to determine the effect of the insertion location of the infusion on the incidence of phlebitis. Design: Literature review method using Google Scholar and the Portal Garuda as databaseÂ  (2018-2022). Method : keywords "location of infusion and phlebitis incident". Results: From 14 reviewed articles, it was found that the incidence of phlebitis due to insertion site factors was influenced by the selection of the vein, the distance between the infusion site and the joint and the selection of the dominant extremity (which is often used for activities). Conclusion: Infusion is done by selecting a good vein, choose a vein that is far from the joint (minimum > 3.5 cm distance from the joint), Avoid choosing a vein in the location or extremity dominant to minimize the movement of the intravenous catheter when the patient moves.